Echographic findings in intraocular parasitosis (1999)
This article describes echographic findings of the intraocular manifestations of toxocariasis and cisticercosis. The records of 21 patients (21 eyes) with the clinical and echographic diagnosis of intraocular parasitosis are reviewed. In order of frequency, the most important echographic findings were vitreous opacities in all patients, granulomas (64%), vitreous membranes (48%), posterior vitreous detachment (28%), vitreoretinal traction (33%), and retinal detachment (38%). Ultrasound is useful in the diagnosis of intraocular parasitosis. It also helps in follow-up and may guide the ophthalmologist in determining appropriate treatment.